Incidência de lesões musculoesqueléticas em árbitros de futebol relacionados a jogos e treinos: estudo de três anos - Vieira, Paulo Rogerio [UNIFESP] (2016)
Introduction: There are many studies on injuries in soccer players, but little work has been done on soccer referees. Objective: To determine the incidence and pain intensity in games and training and places most affected by injuries with musculoskeletal pain, and the incidence and severity of "injuries defined by time off" in games and training in soccer referees of the Federação Paulista, the triennium 2012-2014. Methods: We interviewed 257 referees and used a web application called www.surveymonkey.com. With this tool was sent to referees, a monthly evaluation form with questions that measured incidence, location, pain intensity of injuries as complaints of pain and time off and seriousness in games and practices in the years 2012, 2013 and 2014. To classify pain intensity of injuries with complaints it was used the numerical pain scale. Results: There was no difference between the years studied in relation to the injuries with complaints of pain, both in games and in training and, this showed mean values of 37.8/1000 hours in games and 39.9/1000 hours in training and, the mean incidence of ?injuries defined by time off? was 3.7/1000 hours in games and showed a significantly higher difference in 2013 compared to 2012 and 2014 and, in practice, an incidence of 3.5/1000 hours was observed with a significantly higher difference in 2012 compared to 2013 and 2014. Conclusion: Injuries with complaints of pain have not presented signifcant difference in games compared to training; injuries "defined by time off" incidence was higher in games than in training, and the most common of injury type was muscular with a slight characteristic and predominance in the thigh and triceps surae.